Mathematics
Question:
math help please! math!!!?
?
2011-02-18 20:13:54 UTC
(x-11)/(x+4)=2minus(4/x)
please find the solution set to that. please help!
Four answers:
?
2011-02-18 20:26:27 UTC
(x-11)/(x+4)=2 - (4/x)
x-11 = 2x+8 - ((4x+16)/x)
x²-11x = 2x² + 8x - 4x + 16
0 = x² + 15x + 16
x = approx. -13.8443
^^samira^^ l
2011-02-18 20:26:27 UTC
(x-11)/(x+4)=2-(4/x)
(x-11)/(x+4)= (2x-4)/x
x^2-11x=(2x-4)(x+4)
x^2-11x=2x^2+8x-4x-16
x^2-11x=2x^2+4x-16
0=2x^2-x^2+4x+11x-16
0=x^2+15x-16
0=x^2+16x-x-16
0=x(x+16)-1(x+16)
0=(x+16)(x-1)
therefore,
x+16=0 & x-1=0
x= -16 x=1
solution: x= -16 & x=1
2011-02-18 21:05:11 UTC
This is a really good exam question.
To answer your question visually, Dr. Pan (IvyMathDoc) has recorded a YouTube video. Please follow the link below:
Luis
2011-02-18 20:47:01 UTC
Dear Nicole,
(x-11)/(x+4)=2-((4)/(x))
Least common denominator: (x+4)
(x-11)/(x+4)*(x+4)=2*(x+4)-((4)/(x))*(x+4)
(x-11)/(
(x+4)
)*
(x+4)
=2*(x+4)-((4)/(x))*(x+4)
(x-11)*1=2*(x+4)-((4)/(x))*(x+4)
(x-11)=2*(x+4)-((4)/(x))*(x+4)
x-11=2*(x+4)-((4)/(x))*(x+4)
x-11=2(x+4)-((4)/(x))*(x+4)
x-11=2(x+4)-((4)/(x))(x+4)
x-11=(2(x)+2(4))-((4)/(x))(x+4)
x-11=(2*x+2(4))-((4)/(x))(x+4)
x-11=(2x+2(4))-((4)/(x))(x+4)
x-11=(2x+2*4)-((4)/(x))(x+4)
x-11=(2x+8)-((4)/(x))(x+4)
x-11=(2x+8)-((4)/(x)*x+(4)/(x)*4)
x-11=(2x+8)-((4)/(
x
)*
x
+(4)/(x)*4)
x-11=(2x+8)-(4*1+(4)/(x)*4)
x-11=(2x+8)-(4+(4)/(x)*4)
x-11=(2x+8)-(4+(16)/(x))
x-11=(2x+8)-(4*(x)/(x)+(16)/(x))
x-11=(2x+8)-((4x)/(x)+(16)/(x))
x-11=(2x+8)-((4x+16)/(x))
x-11=(2x+8)-((4(x)+16)/(x))
x-11=(2x+8)-((4(x)+4(4))/(x))
x-11=(2x+8)-((4(x+4))/(x))
x-11=(2x+8)-(4(x+4))/(x)
x-11=2x+8-(4(x+4))/(x)
x-11=2x*(x)/(x)+8*(x)/(x)-(4(x+4))/(x)
x-11=(2x*x)/(x)+8*(x)/(x)-(4(x+4))/(x)
x-11=(2x^(2))/(x)+8*(x)/(x)-(4(x+4))/(x)
x-11=(2x^(2))/(x)+(8*x)/(x)-(4(x+4))/(x)
x-11=(2x^(2))/(x)+(8x)/(x)-(4(x+4))/(x)
x-11=((2x^(2))+(8x)-4(x+4))/(x)
x-11=(2x^(2)+(8x)-4(x+4))/(x)
x-11=(2x^(2)+8x-4(x+4))/(x)
x-11=(2x^(2)+8x+(-4(x)-4(4)))/(x)
x-11=(2x^(2)+8x+(-4*x-4(4)))/(x)
x-11=(2x^(2)+8x+(-4x-4(4)))/(x)
x-11=(2x^(2)+8x+(-4x-4*4))/(x)
x-11=(2x^(2)+8x+(-4x-16))/(x)
x-11=(2x^(2)+8x-4x-16)/(x)
x-11=(2x^(2)+(8-4)x-16)/(x)
x-11=(2x^(2)+(4)x-16)/(x)
x-11=(2x^(2)+4x-16)/(x)
x-11=(2(x^(2))+4x-16)/(x)
x-11=(2(x^(2))+2(2x)-16)/(x)
x-11=(2(x^(2))+2(2x)+2(-8))/(x)
x-11=(2(x^(2)+2x-8))/(x)
x-11=(2(x+4)(x-2))/(x)
(2(x+4)(x-2))/(x)=x-11
Least common denominator: x
(2(x+4)(x-2))/(x)*x=x*x-11*x
(2(x+4)(x-2))/(
x
)*
x
=x*x-11*x
2(x+4)(x-2)=x*x-11*x
2(x*x+x*-2+4*x+4*-2)=x*x-11*x
2(x^(2)+x*-2+4*x+4*-2)=x*x-11*x
2(x^(2)-2x+4*x+4*-2)=x*x-11*x
2(x^(2)-2x+4x+4*-2)=x*x-11*x
2(x^(2)-2x+4x-8)=x*x-11*x
2(x^(2)+(-2+4)x-8)=x*x-11*x
2(x^(2)+(2)x-8)=x*x-11*x
2(x^(2)+2x-8)=x*x-11*x
(2(x^(2))+2(2x)+2(-8))=x*x-11*x
(2*x^(2)+2(2x)+2(-8))=x*x-11*x
(2x^(2)+2(2x)+2(-8))=x*x-11*x
(2x^(2)+2*2x+2(-8))=x*x-11*x
(2x^(2)+4x+2(-8))=x*x-11*x
(2x^(2)+4x-2*8)=x*x-11*x
(2x^(2)+4x-16)=x*x-11*x
2x^(2)+4x-16=x*x-11*x
2x^(2)+4x-16=x^(2)-11*x
2x^(2)+4x-16=x^(2)-11x
2x^(2)+4x-16-x^(2)=-11x
2x^(2)+4x-16-x^(2)+11x=0
(2-1)x^(2)+4x-16+11x=0
(1)x^(2)+4x-16+11x=0
x^(2)+4x-16+11x=0
x^(2)+(4+11)x-16=0
x^(2)+(15)x-16=0
x^(2)+15x-16=0
(x+16)(x-1)=0
x+16=0_x-1=0
x=-16_x-1=0
x=-16_x-1=0
x=-16_x=1
x=-16,1
ⓘ
This content was originally posted on Y! Answers, a Q&A website that shut down in 2021.
Loading...